Spanish in the southwest - Sanchez, George I. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1965)
In the American southwest, four million Spanish-Americans are concentrated in five states. Their cultural tenacity is a peculiarity not displayed by other immigrant groups. Even after 125 years they speak and live in a Spanish-American society. The reason for this is difficult to discern, but it is felt by some that this tenacity is very noble and laudable. In attempting to explain the Spanish-American society, the author gives a history of the Spanish language from the time of the moor influence in spain to the influx of Spanish-speaking peoples into the southwest. The problem of acculturation is discussed. The second part of the report is concerned with bi-lingualism in education. It is pointed out that a rich culture lies unharvested by the present educational system. The true problem in the school is not linguistic but is one of social policy in school organization which results in teaching handicaps. Although the educational level of the Mexican-American is statistically quite low, it contrasts sharply with his lingual proficiency in his native vernacular. The reason for this lies with his isolated position in American society. It should be realized that bilingualism and multilingualism are of great value in our relations with the rest of the world.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Students; Cultural Background; Cultural Influences; Educational Policy; Language Skills; Mexican Americans; Spanish; Spanish Culture